2018
DOI: 10.1002/hbm.23955
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal fronto‐striatal activation as a marker of threshold and subthreshold Bulimia Nervosa

Abstract: This study aimed to determine whether functional disturbances in fronto-striatal control circuits characterize adolescents with Bulimia Nervosa (BN) spectrum eating disorders regardless of clinical severity. FMRI was used to assess conflict-related brain activations during performance of a Simon task in two samples of adolescents with BN symptoms compared with healthy adolescents. The BN samples differed in the severity of their clinical presentation, illness duration and age. Multi-voxel pattern analyses (MVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 59 publications
1
20
2
Order By: Relevance
“…In BN compared to AN, deactivation of parietal cortex and dorsal posterior cingulate cortex (somatosensory areas), and greater activation of the striatum (reward/motivation processing), superior temporal gyrus, right insula (associated with anxiety) and supplementary motor area (linked to uncontrolled decision-making behaviour) was observed. These regional activation differences are in line with recent, more sophisticated analyses of neural processes in BN using multi-variate analyses based on machine learning [ 4 ]. Cyr and colleagues demonstrated that women with BN show diminished recruitment of prefrontal cortex circuitry and deficient regulation of the striatum by the prefrontal regions that may classify both chronic and sub-threshold BN with lower disorder severity.…”
supporting
confidence: 83%
“…In BN compared to AN, deactivation of parietal cortex and dorsal posterior cingulate cortex (somatosensory areas), and greater activation of the striatum (reward/motivation processing), superior temporal gyrus, right insula (associated with anxiety) and supplementary motor area (linked to uncontrolled decision-making behaviour) was observed. These regional activation differences are in line with recent, more sophisticated analyses of neural processes in BN using multi-variate analyses based on machine learning [ 4 ]. Cyr and colleagues demonstrated that women with BN show diminished recruitment of prefrontal cortex circuitry and deficient regulation of the striatum by the prefrontal regions that may classify both chronic and sub-threshold BN with lower disorder severity.…”
supporting
confidence: 83%
“…As noted above, asymmetrical Simon effects between hemifields were found in two previous behavioral studies that used a unimanual Simon task, with smaller mean Simon effects on the side of the responding hand 45,72 . Still, other fMRI studies using unimanual variants of the Simon task did not report asymmetries in task performance 39,[77][78][79] . To our knowledge, there are currently no studies available that analyzed the time course of the Simon effect across the RT distribution as a function of lateralized visual stimuli (neither for bimanual nor unimanual response set-ups).…”
Section: Discussionmentioning
confidence: 86%
“…89,90 Machine learning approaches using these altered patterns of activation can reliably distinguish BN cases from healthy controls. 91,92 One study has used a go/no-go task to examine differences in response inhibition to food and neutral images and found that only a BN subgroup with the most frequent binge eating showed decreased activation during response inhibition to neutral images in dorsal striatum, with additional hypoactivation in sensorimotor areas. 92 One emotional go/no-go study found that individuals with BN showed age-dependent deficits in PFC activation during emotional go/no-go task response inhibition relative to healthy controls.…”
Section: Brain Studies: Bulimia Nervosamentioning
confidence: 99%